Slow walking speed and cardiovascular death in well functioning older adults: prospective cohort study. (10th November 2009) - Dumurgier, Julien; Elbaz, Alexis; Ducimetière, Pierre; Tavernier, Béatrice; Alpérovitch, Annick; Tzourio, Christophe
Abstract : Objective To study the relation between low walking speed and the risk of death in older people, both overall and with regard to the main causes of death. Design Prospective cohort study. Setting Dijon centre (France) of the Three-City study. Participants 3208 men and women aged ≥65 living in the community, recruited from 1999 to 2001, and followed for an average of 5.1 years. Main outcome measures Mortality, overall and according to the main causes of death, by thirds of baseline walking speed (measured at maximum speed over six metres), adjusted for several potential confounders; Kaplan-Meier survival curves by thirds of baseline walking speed. Vital status during follow-up. Causes of death. Results During 16 414 person years of follow-up, 209 participants died (99 from cancer, 59 from cardiovascular disease, 51 from other causes). Participants in the lowest third of baseline walking speed had an increased risk of death (hazard ratio 1.44, 95% confidence interval 1.03 to 1.99) compared with the upper thirds. Analyses for specific causes of death showed that participants with low walking speed had about a threefold increased risk of cardiovascular death (2.92, 1.46 to 5.84) compared with participants who walked faster. There was no relation with cancer mortality (1.03, 0.65 to 1.70). In stratified analyses, cardiovascular mortality was increased across various strata defined by sex, median age, median body mass index (BMI), and level of physical activity. Conclusion Slow walking speed in older people is strongly associated with an increased risk of cardiovascular mortality.